Aggregate Uncertainty and Sectoral Productivity Growth : The Role of Credit Constraints - Choi, Sangyup (IMF Working Papers; Working Paper ;, 2016)
We show that an increase in aggregate uncertainty-measured by stock market volatility-reduces productivity growth more in industries that depend heavily on external finance. This effect is larger during recessions, when financing constraints are more likely to be binding, than during expansions. Our statistical method-a difference-in-difference approach using productivity growth for 25 industries for 18 advanced economies over the period 1985-2010-mitigates concerns with omitted variable bias and reverse causality. The results are robust to the inclusion of other sources of interaction effects, such as financial development (Rajan and Zingales, 1998) and counter-cyclical fiscal policy (Aghion and others, 2014). The results also hold if economic policy uncertainty (Baker and others, 2015) is used instead of stock market volatility as the measure of aggregate uncertainty.